Porous adsorption material for removing neon in helium and preparation method of porous adsorption material

Through composite microbial fermentation treatment and metal ions in situ oriented activation pore formation methods, porous carbon materials with uniform pore size distribution were prepared, which solved the problem of low adsorption capacity of commercial activated carbon on neon gas and achieved efficient neon gas adsorption effect, especially under low temperature and low pressure conditions.

CN119633756AActive Publication Date: 2025-03-18广州广钢气体能源股份有限公司 +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510174019.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-18
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

In the prior art, commercial activated carbon adsorbents have low adsorption capacity to neon gas, resulting in difficult to improve the production efficiency of high-purity helium and poor effect under low pressure conditions.

Method used

Compound microorganisms are used to ferment the lignin raw materials to prepare porous carbon materials with uniform pore size distribution, and pore formation is activated by metal ions in situ to improve the neon adsorption ability of the material at low temperature and low pressure.

Benefits of technology

The adsorption amount of neon gas of porous adsorbent materials under low temperature and low pressure conditions was significantly improved, and the adsorption amount could reach 0.87 mmol/g, which was far higher than the 0.45 mmol/g of commercial coconut shell CTC100 activated carbon, improving the efficiency and selectivity of high-purity helium production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633756A_ABST
    Figure CN119633756A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of special gas purification, and particularly discloses a porous adsorption material for removing neon in helium and a preparation method of the porous adsorption material. The method comprises the following steps: (1) preparing a lignin raw material subjected to fermentation treatment; (2) preparing a carbon precursor; (3) placing the carbon precursor in a mixed solution containing a metal salt and a surfactant, stirring and dipping to obtain a metal salt dipped carbon precursor; (4) washing the metal salt impregnated carbon precursor, removing excessive deposited metal salt, and drying to obtain a cleaned carbon precursor; and (5) carrying out activated pore-forming on the cleaned carbon precursor by using carbon dioxide at a high temperature to obtain the porous adsorption material for removing neon in helium. The porous carbon adsorption material prepared from renewable natural biomass raw materials has a uniformly distributed pore diameter structure, has very high adsorption and capture capability on neon gas under a low-temperature condition, and can effectively remove neon gas impurities in helium gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of special gas purification, and specifically relates to a porous adsorption material for removing neon from helium, and a preparation method and application thereof. Background Art

[0002] Helium (He) is a colorless and odorless inert gas, which is widely used in many fields such as semiconductors, medical treatment, military industry, aerospace, etc. It is one of the rare strategic materials indispensable for the development of high-tech industries. With the rapid development of domestic high-tech industries, the market demand for high-purity helium is also increasing.

[0003] Since the content of helium in the air is extremely low, only about 5ppm, it is difficult to effectively produce helium using traditional air fractionation equipment. Therefore, the current helium is mainly obtained by condensing natural gas step by step to about -190℃ to obtain crude helium with a purity of 70% to 90%, and then further purified into 99.999% high-purity helium by cryogenic distillation. However, since the boiling point of helium is very low (-268.9℃), and the boiling point of neon, the main impurity in crude helium, is also relatively low (-248.6℃), deep cooling methods are required to separate neon and helium and produce high-purity helium. This is a production process with large equipment investment and extremely high energy consumption. The low-temperature adsorption method can be used to adsorb and remove impurities such as neon in helium under low-temperature conditions, so that the purity of helium can be increased to 99.999%, which can significantly improve the production efficiency of neon and greatly reduce production energy consumption.

[0004] Chinese invention patent application CN202311869986.1 discloses a low-temperature pressure swing adsorption method for efficiently removing neon and hydrogen from helium. The raw gas containing helium and impurity gases can be subjected to the designed pressure swing adsorption process to reduce the concentration of neon and hydrogen to below 4ppm and 1ppm respectively. However, the current commercial activated carbon adsorbent has a low adsorption capacity for neon, making it difficult to improve production efficiency.

[0005] Porous carbon materials have the advantages of large specific surface area and pore volume, stable structure and low production cost, and have broad application prospects in the field of gas separation and purification. Activated carbon is one of the most commonly used raw materials for existing low-temperature adsorbents. The temperature is 60-77K near the liquid nitrogen temperature zone, and it has been industrialized. However, powdered activated carbon usually has a very high specific surface area and rich microporous structure, which makes them excellent in gas adsorption; but in order to make powdered activated carbon into easy-to-handle block or granular materials, it is usually necessary to add a binder, which may fill or cover the micropores of the activated carbon, thereby reducing the effective adsorption sites, reducing the adsorption capacity and selectivity. At present, the porous carbon materials used to produce high-purity helium are mostly commercial activated carbons with a wide pore size distribution, which leads to their low adsorption capacity for the inert gas neon, greatly limiting the efficiency of producing high-purity helium by low-temperature adsorption. The carbon-based adsorbents directly prepared by the current methods on the market often lack sufficient mechanical strength and are easily broken into powder during operation, resulting in decreased adsorption performance; the direct preparation method may lead to uneven pore size distribution, affecting the selectivity and adsorption efficiency of specific gases. Therefore, the current low-temperature adsorption method still has small adsorption capacity and low recovery rate. At the same time, the effect of current adsorbents under low pressure cannot meet the needs of consumers.

[0006] Therefore, there is an urgent need for a porous carbon material with uniform pore size distribution and high adsorption capacity for the inert gas neon at low temperature and a preparation method thereof. Summary of the invention

[0007] Based on the deficiencies of the prior art, the present invention provides a porous carbon material with uniform pore size distribution and high adsorption capacity for inert gas neon at low temperature and a preparation method thereof.

[0008] In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing a porous adsorption material for removing neon from helium comprises the following steps: (1) crushing the lignin raw material to less than 200 meshes to obtain powder; mixing 20-30 parts of the powder and 40-50 parts of deionized water by weight to obtain a fermentation material, inoculating the fermentation material with mixed microorganisms for aerobic fermentation, filtering, drying, crushing, screening, and obtaining a fermented lignin raw material; the mixed microorganisms include Bacillus licheniformis, Bacillus subtilis, and Rhizopus oryzae; (2) Mixing 1 part by weight of the fermented lignin raw material and 10-12 parts by weight of 1-1.2 mol / L hydrochloric acid, ultrasonically dispersing the mixture at a power of 90-100 W for 40-50 min, stirring the mixture at 80-85 ° C and a speed of 600-650 rpm for 25-30 h, washing the mixture with deionized water until neutral, and vacuum drying the mixture in a vacuum drying oven at 80-90 ° C for 24-28 h to obtain a carbon precursor; (3) placing the carbon precursor in a mixed solution containing a metal salt and a surfactant and stirring and impregnating the mixture to obtain a metal salt-impregnated carbon precursor; (4) washing the carbon precursor impregnated with the metal salt to remove the excess deposited metal salt, and drying to obtain a cleaned carbon precursor; (5) The cleaned carbon precursor is activated with carbon dioxide to form pores, thereby obtaining a porous adsorption material for removing neon from helium, which is labeled as MC.

[0009] Furthermore, the amount of Bacillus licheniformis used in step (1) is 10 8 -10 9 CFU / mL fermentation feed; the dosage of Bacillus subtilis is 10 6 -10 7 CFU / mL fermentation feed; the dosage of Rhizopus oryzae is 10 6 -10 7 CFU / mL fermentation feed.

[0010] The present invention uses composite microorganisms to first ferment lignin raw materials to prepare porous adsorption materials, which can improve the neon adsorption capacity of porous adsorption materials under 10000Pa conditions. Bacillus licheniformis, Bacillus subtilis and Rhizopus oryzae can secrete a variety of enzymes during aerobic fermentation, which can partially degrade the complex structure inside the lignin raw materials. After fermentation treatment, its molecular chains are partially interrupted and chemical bonds are broken, so that the structure of lignin changes, providing more abundant micropores and mesoporous structures, and the synergistic effect of these pores can significantly increase the specific surface area of ​​the adsorption material. A larger specific surface area means more adsorption sites, thereby increasing the adsorption capacity of the adsorption material for neon.

[0011] Furthermore, the lignin raw material in step (1) comprises coconut shell, olive shell and bamboo in a weight ratio of 1: (1.3-1.5): (0.5-0.7).

[0012] When coconut shell, olive shell and bamboo are used as lignin raw materials in a specific ratio, the adsorption of neon under 1000Pa can be further improved. This is mainly because the lignin content and structure in coconut shell, olive shell and bamboo are different. Coconut shell is easy to form larger mesopores and macropores during fermentation and activation, which is conducive to the diffusion and adsorption of gas molecules; olive shell is more likely to form micropores, which can provide more high-energy adsorption sites, especially suitable for adsorption of neon; bamboo can form uniformly distributed micropores and mesopores during fermentation and activation. The diversity of this pore structure helps to improve the specific surface area and adsorption selectivity of the adsorption material. The complementarity of different raw materials, the synergistic effect of microbial metabolites, the optimized pore structure and adsorption sites, and the improved mechanical strength and stability work together to make the adsorption material show higher adsorption performance under medium partial pressure conditions. This improvement not only improves the adsorption capacity of the adsorption material, but also enhances its selectivity and stability.

[0013] Bacillus licheniformis was purchased from Shanghai Baocang Microbiology Co., Ltd., product number: SHMCCD10742.

[0014] Bacillus subtilis was purchased from Shanghai Baocang Microorganism Co., Ltd., product number: SHMCCD15537.

[0015] Rhizopus oryzae was purchased from Shanghai Baocang Microbiology Co., Ltd., product number: SHMCCD10257.

[0016] Furthermore, the fermentation conditions in step (1) are: fermentation at 32-35° C. for 5-8 hours.

[0017] Furthermore, the surfactant in step (3) comprises sodium dodecylbenzene sulfonate, octadecyl dimethyl betaine and a zwitterionic surfactant in a weight ratio of 1: (1.2-1.4): (0.3-0.5); the mass fraction of the surfactant in the mixed solution is 0.5-2.5%.

[0018] Furthermore, the preparation method of the zwitterionic surfactant comprises the following steps: Step 1: Heat the HCl aqueous solution to 40-45°C, add N,N-dimethylhexadecylamine dropwise, keep warm for 1-1.5h, then add ethanol solution of epoxidized soybean oil dropwise, control the temperature at 50-55°C, react for 6-8h, remove ethanol and water by vacuum distillation, and obtain soybean oil-based butylamine salt; in terms of molar ratio, N,N-dimethylhexadecylamine: HCl: epoxidized soybean oil = 3:3: (0.8-1); Step 2: Dissolve 10 parts by weight of soybean oil octylamine salt in ethanol aqueous solution, add 0.5-0.7 parts by weight of NaOH, reflux and stir for 4-6 hours, stop the reaction, filter, wash the filter residue with anhydrous ethanol 3-4 times, and vacuum dry to obtain a zwitterionic surfactant.

[0019] The present invention can improve the adsorption capacity of neon gas at low pressure (100Pa) by adding a surfactant of a specific ratio to the impregnation solution. The addition of the surfactant used in the present invention can play a dispersing role in the metal salt deposition process, prevent the aggregation of metal salt particles, and ensure that they are evenly distributed on the surface and inside the pores of the carbon precursor prepared by the present invention, which can further optimize the pore structure, increase the adsorption sites and improve the adsorption selectivity, which helps to maintain the openness of the pores and avoid pore blockage.

[0020] Furthermore, the metal salt in step (3) is selected from one or more of sodium salt, potassium salt, magnesium salt and zinc salt.

[0021] Furthermore, the concentration of the metal salt in the mixed solution in step (3) is 1-5 mol / L.

[0022] Furthermore, the stirring and impregnation conditions in step (3) are: impregnation time is 20-24h, temperature is 60-80°C, and stirring speed is 200-300rpm.

[0023] Furthermore, the impregnation solid-liquid ratio of the carbon precursor and the mixed solution in step (3) is 1 g:15 mL to 1 g:20 mL.

[0024] Furthermore, in step (5), the activation pore-forming process is to heat the cleaned carbon precursor and use carbon dioxide to activate the pore-forming process, the heating rate is 5-10°C / min, the activation temperature is 800-1000°C, the activation time is 80-100min, and the carbon dioxide concentration is 80-100%.

[0025] The invention provides a porous adsorption material for removing neon from helium, which is prepared by the preparation method.

[0026] Compared with the prior art, the present invention has the following advantages and technical effects: (1) The present invention utilizes bamboo, coconut shell, and olive shell containing lignin as carbon sources, and adopts a method of in-situ directional activation of metal ions to form pores. During the physical activation and pore-forming process of the porous carbon material, highly dispersed metal ions are used to perform in-situ etching and activation on the porous carbon material, thereby controlling the activation and pore-forming reaction of the porous carbon material, and preparing a porous carbon adsorption material with uniform pore size distribution. The porous carbon adsorption material has a high adsorption and capture ability for neon under low temperature conditions, and can effectively remove neon impurities in helium.

[0027] (2) The present invention provides a porous adsorption material for removing neon from helium, which can use natural biomass materials as carbon sources, is green, environmentally friendly, renewable, and has low production costs. The adsorption material of the present invention uses the method of in-situ directional activation of metal ions to form pores, and accurately etches uniform pores on the carbon material. Compared with commercial activated carbon, the pore size distribution of the adsorption material of the present invention is more uniform, so that it has a stronger neon adsorption capacity.

[0028] (3) The present invention uses composite microorganisms to ferment lignin raw materials to prepare porous adsorption materials, which can improve the neon adsorption capacity of the porous adsorption materials under 10000Pa. Compared with existing adsorption materials, the adsorption capacity of the adsorption material of the present invention for 0.1bar neon at low temperature can reach 0.87mmol / g, which is much higher than 0.45mmol / g of commercial coconut shell CTC100 activated carbon.

[0029] (4) When a specific ratio of coconut shell, olive shell and bamboo is used as lignin raw materials, the neon adsorption capacity under 1000Pa conditions can be further improved.

[0030] (5) The present invention can improve the adsorption capacity of neon gas at low pressure (100 Pa) by adding a surfactant of a specific ratio to the impregnation solution. The adsorption material of the present invention can have an excellent adsorption effect under low temperature and low pressure conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a typical pore size distribution diagram of commercial coconut shell activated carbon CTC100 and the adsorption material obtained in Example 4.

[0032] Figure 2 The isotherms of C3H8 and CH3F adsorption at 298K for commercial coconut shell activated carbon CTC100 and the adsorbent materials obtained in Examples 1-5 of the present invention. In the figure, MC-1 is the porous adsorbent material prepared in Example 1, MC-2 is the porous adsorbent material prepared in Example 2, MC-3 is the porous adsorbent material prepared in Example 3, MC-4 is the porous adsorbent material prepared in Example 4, and MC-5 is the porous adsorbent material prepared in Example 5. DETAILED DESCRIPTION

[0033] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments, but the scope of protection claimed by the present invention is not limited to the scope described in the embodiments.

[0034] The raw materials used in the present invention are all commercially available products: Bacillus licheniformis was purchased from Shanghai Baocang Microbiology Co., Ltd., product number: SHMCCD10742.

[0035] Bacillus subtilis was purchased from Shanghai Baocang Microorganism Co., Ltd., product number: SHMCCD15537.

[0036] Rhizopus oryzae was purchased from Shanghai Baocang Microbiology Co., Ltd., product number: SHMCCD10257.

[0037] Epoxidized soybean oil was purchased from Shandong Kexing Chemical Co., Ltd., industrial grade epoxidized soybean oil.

[0038] Aspergillus niger was purchased from Shanghai Baocang Microbiology Co., Ltd., product number: SHMCC D11656.

[0039] Candida utilis was purchased from Wuhan Huizao Biotechnology Co., Ltd., catalog number: HZB119504.

[0040] Example 1

[0041] This embodiment provides a porous adsorption material for removing neon from helium, and the preparation method thereof comprises the following steps: (1) crushing the lignin raw material to less than 200 meshes to obtain powder; mixing 20 parts of the powder and 50 parts of deionized water by weight to obtain a fermentation material, inoculating the fermentation material with mixed microorganisms for aerobic fermentation under the following fermentation conditions: fermentation at 32° C. for 8 hours; filtering, drying, crushing and screening powder between 100 and 200 meshes to obtain a fermented lignin raw material; the mixed microorganisms include Bacillus licheniformis, Bacillus subtilis and Rhizopus oryzae; The lignin raw materials include coconut shells, olive shells and bamboo in a weight ratio of 1:1.3:0.5.

[0042] The dosage of Bacillus licheniformis is 10 8 CFU / mL fermentation feed; the dosage of Bacillus subtilis is 10 7 CFU / mL fermentation feed; the dosage of Rhizopus oryzae is 10 6 CFU / mL fermentation feed.

[0043] (2) Mixing 1 part by weight of the fermented lignin raw material and 12 parts by weight of 1 mol / L hydrochloric acid, ultrasonically dispersing the mixture at a power of 100 W for 40 min, stirring the mixture at 85 ° C and a speed of 600 rpm for 30 h, washing the mixture with deionized water until neutral, and vacuum drying the mixture in a vacuum drying oven at 80 ° C for 28 h to obtain a carbon precursor; (3) placing the carbon precursor in a mixed solution containing a metal salt and a surfactant and stirring and impregnating the carbon precursor. The stirring and impregnation conditions are: impregnation time is 20 hours, temperature is 80°C, and stirring speed is 200 rpm. The impregnation solid-liquid ratio of the carbon precursor and the mixed solution is 1g:15mL; obtaining a metal salt-impregnated carbon precursor; The metal salt is potassium chloride; the concentration of the metal salt in the mixed solution is 5 mol / L; the surfactant comprises sodium dodecylbenzene sulfonate, octadecyl dimethyl betaine and a zwitterionic surfactant in a weight ratio of 1:1.2:0.3; the mass fraction of the surfactant in the mixed solution is 1%; and the balance of the mixed solution is water.

[0044] The preparation method of the zwitterionic surfactant comprises the following steps: Step 1: Heat 100 mL of 5.5 mol / L HCl aqueous solution to 40°C, add 0.5 mol of N,N-dimethylhexadecylamine dropwise, and react for 1.5 hours at this temperature. Then, add 1.5 mol of ethanol solution containing 55% by volume of epoxy soybean oil dropwise, control the temperature at 55°C, react for 6 hours, and remove ethanol and water by vacuum distillation to obtain soybean oil-based butylamine salt; Step 2: Dissolve 10 g of soybean oil octylamine salt in 220 mL of 90% ethanol aqueous solution, add 0.7 g of NaOH, reflux and stir for 4 h, stop the reaction, filter, wash the filter residue with anhydrous ethanol three times, and vacuum dry to obtain a zwitterionic surfactant.

[0045] (4) washing the carbon precursor impregnated with the metal salt with water to remove the excess deposited metal salt, and drying to obtain a cleaned carbon precursor; (5) The cleaned carbon precursor is activated with carbon dioxide at high temperature to form pores. The heating rate of the high temperature activation is 10°C / min, the activation temperature is 800°C, the activation time is 100 min, and the carbon dioxide concentration is 80%; a porous adsorption material for removing neon from helium is obtained.

[0046] Example 2

[0047] The difference between this embodiment and embodiment 1 is that the surfactant in step (3) comprises sodium dodecylbenzene sulfonate, octadecyl dimethyl betaine and a zwitterionic surfactant in a weight ratio of 1:1.2:0.3; and the preparation method of the zwitterionic surfactant is the same as that in embodiment 1.

[0048] Example 3

[0049] The difference between this embodiment and embodiment 1 is that the lignin raw material includes coconut shell, olive shell and bamboo in a weight ratio of 1:1.3:0.5.

[0050] Example 4

[0051] This embodiment provides a porous adsorption material for removing neon from helium, and the preparation method thereof comprises the following steps: (1) crushing the lignin raw material to less than 200 meshes to obtain powder; mixing 25 parts of the powder and 45 parts of deionized water by weight to obtain a fermentation material, inoculating mixed microorganisms into the fermentation material for aerobic fermentation under the following fermentation conditions: fermentation at 33° C. for 6 hours; filtering, drying, and crushing to 100-200 meshes to obtain a fermented lignin raw material; the mixed microorganisms include Bacillus licheniformis, Bacillus subtilis, and Rhizopus oryzae; The lignin raw materials include coconut shell, olive shell and bamboo in a weight ratio of 1:1.4:0.6.

[0052] The dosage of Bacillus licheniformis is 10 8 CFU / mL fermentation feed; the dosage of Bacillus subtilis is 10 7 CFU / mL fermentation feed; the dosage of Rhizopus oryzae is 10 6 CFU / mL fermentation feed.

[0053] (2) 1 part by weight of the fermented lignin raw material and 11 parts by weight of 1.1 mol / L hydrochloric acid were mixed, ultrasonically dispersed at a power of 95 W for 45 min, stirred at 82 ° C and a speed of 620 rpm for 27 h, washed with deionized water until neutral, and vacuum dried in a vacuum drying oven at 85 ° C for 26 h to obtain a carbon precursor; (3) placing the carbon precursor in a mixed solution containing a metal salt and a surfactant and stirring and impregnating the carbon precursor. The stirring and impregnation conditions are: impregnation time is 22 hours, temperature is 70°C, and stirring speed is 250rpm. The impregnation solid-liquid ratio of the carbon precursor and the mixed solution is 1:18g / mL; obtaining a metal salt-impregnated carbon precursor; The metal salt is sodium chloride. The concentration of the metal salt in the mixed solution is 2 mol / L.

[0054] The surfactant comprises sodium dodecylbenzene sulfonate, octadecyl dimethyl betaine and a zwitterionic surfactant in a weight ratio of 1:1.3:0.4; the mass fraction of the surfactant in the mixed solution is 2%.

[0055] The preparation method of the zwitterionic surfactant comprises the following steps: Step 1: Heat 100 mL of 5.2 mol / L HCl aqueous solution to 42°C, add 0.5 mol of N,N-dimethylhexadecylamine, and react for 1.2 hours. Then, add 1.5 mol of ethanol solution containing 58% by volume of epoxy soybean oil, control the temperature at 52°C, react for 7 hours, and remove ethanol and water by vacuum distillation to obtain soybean oil-based butylamine salt; Step 2: Dissolve 10 g of soybean oil octylamine salt in 210 mL of 92% ethanol aqueous solution, add 0.6 g of NaOH, reflux and stir for 5 h, stop the reaction, filter, wash the filter residue with anhydrous ethanol 4 times, and vacuum dry to obtain a zwitterionic surfactant.

[0056] (4) washing the carbon precursor impregnated with the metal salt with water to remove the excess deposited metal salt, and drying to obtain a cleaned carbon precursor; (5) The cleaned carbon precursor is activated with carbon dioxide at high temperature to form pores. The heating rate of the high temperature activation is 7°C / min, the activation temperature is 900°C, the activation time is 90 min, and the carbon dioxide concentration is 90%; a porous adsorption material for removing neon from helium is obtained.

[0057] Example 5

[0058] The difference between this embodiment and embodiment 1 is that the amount of Bacillus licheniformis used in step (1) is 10 9 CFU / mL fermentation feed; the dosage of Bacillus subtilis is 10 7 CFU / mL fermentation feed; the dosage of Rhizopus oryzae is 10 7 CFU / mL fermentation feed.

[0059] Comparative Example 1 The difference between this comparative example and Example 4 is that the surfactant in step (3) comprises sodium dodecylbenzene sulfonate, octadecyl dimethyl betaine and a zwitterionic surfactant in a weight ratio of 1:1:1; and the preparation method of the zwitterionic surfactant is the same as that of Example 1.

[0060] Comparative Example 2 The difference between this comparative example and Example 4 is that the surfactant in step (3) includes sodium fatty alcohol polyoxyethylene ether sulfate (purchased from Jinan Saijia Chemical Co., Ltd.), ammonium monococoglyceryl sulfate (CAS: 61789-03-5) and sodium dodecyl sulfate in a weight ratio of 1:1.2:0.3.

[0061] Comparative Example 3 The difference between this comparative example and Example 4 is that the mixed microorganisms include Candida utilis, Bacillus subtilis and Aspergillus niger; the dosage of Candida utilis is 10 8 CFU / mL fermentation feed; the dosage of Bacillus subtilis is 10 7 CFU / mL fermentation feed; the dosage of Aspergillus niger is 10 6 CFU / mL fermentation feed.

[0062] Comparative Example 4 The difference between this comparative example and Example 4 is that the stirring and impregnation conditions are: the impregnation time is 15 hours, the temperature is 85° C., and the stirring speed is 400 rpm; the impregnation solid-liquid ratio of the carbon precursor and the mixed solution is 1:10 g / mL.

[0063] Comparative Example 5 The difference between this comparative example and Example 4 is that the heating rate of high-temperature activation in step (5) is 15°C / min, the activation temperature is 600°C, the activation time is 60 min, and the carbon dioxide concentration is 50%.

[0064] Comparative Example 6 The difference between this comparative example and Example 4 is that no fermentation treatment is performed.

[0065] (1) 1 part by weight of lignin raw material and 11 parts by weight of 1.1 mol / L hydrochloric acid were mixed, ultrasonically dispersed at a power of 95 W for 45 min, stirred at 82 ° C and a speed of 620 rpm for 27 h, washed with deionized water until neutral, and vacuum dried in a vacuum drying oven at 85 ° C for 26 h to obtain a carbon precursor; (2) placing the carbon precursor in a mixed solution containing a metal salt and a surfactant and stirring and impregnating the carbon precursor. The stirring and impregnation conditions are: impregnation time is 22 hours, temperature is 70°C, and stirring speed is 250rpm. The impregnation solid-liquid ratio of the carbon precursor and the mixed solution is 1:18g / mL; obtaining a metal salt-impregnated carbon precursor; The metal salt is sodium chloride. The concentration of the metal salt in the mixed solution is 2 mol / L.

[0066] The surfactant comprises sodium dodecylbenzene sulfonate, octadecyl dimethyl betaine and a zwitterionic surfactant in a weight ratio of 1:1.3:0.4; The preparation method of the zwitterionic surfactant comprises the following steps: Step 1: Heat 100 mL of 5.2 mol / L HCl aqueous solution to 42°C, add 0.5 mol of N,N-dimethylhexadecylamine, and react for 1.2 hours. Then, add 1.5 mol of ethanol solution containing 58% by volume of epoxy soybean oil, control the temperature at 52°C, react for 7 hours, and remove ethanol and water by vacuum distillation to obtain soybean oil-based butylamine salt; Step 2: Dissolve 10 g of soybean oil octylamine salt in 210 mL of 92% ethanol aqueous solution, add 0.6 g of NaOH, reflux and stir for 5 h, stop the reaction, filter, wash the filter residue with anhydrous ethanol 4 times, and vacuum dry to obtain a zwitterionic surfactant.

[0067] (3) washing the carbon precursor impregnated with the metal salt to remove the excessively deposited metal salt, and drying to obtain a cleaned carbon precursor; (4) The cleaned carbon precursor is activated with carbon dioxide at high temperature to form pores. The heating rate of the high temperature activation is 7°C / min, the activation temperature is 900°C, the activation time is 90 min, and the carbon dioxide concentration is 90%; a porous adsorption material for removing neon from helium is obtained.

[0068] Performance Testing 1. The pore size distribution of commercial coconut shell activated carbon CTC100 and the porous carbon adsorption material MC prepared in Example 4 was analyzed using the ASAP2460 multi-station fully automatic specific surface and pore size analyzer from Micromeritics, USA. The results are shown in Figure 1 The results show that the pore size of the porous carbon adsorption material MC prepared in Example 4 of the present invention is concentrated at 6.8Å. The carbon material can be directionally etched to form pores by using highly dispersed metal ions, so that the prepared porous carbon adsorption material MC has a uniform and concentrated pore size distribution and has excellent adsorption capacity for neon.

[0069] 2. The neon adsorption capacity of commercial coconut shell activated carbon CTC100, the porous carbon adsorption materials prepared in Examples 1-5 and Comparative Examples 1-6 at 77K under partial pressures of 10000Pa, 1000Pa and 100Pa, and the neon adsorption isotherms of Examples 1-5 were measured using a 3Flex three-station gas adsorption instrument from Micromeritics, USA. The results are shown in Tables 1 and Figure 2 .

[0070] Table 1. Test results of neon adsorption at 77K (mmol / g)

[0071] The results show that the neon adsorption capacity of the porous carbon adsorption materials prepared in Examples 1 to 5 is higher than that of the commercial coconut shell activated carbon CTC100 at different partial pressures. In particular, Example 4 has the best overall adsorption effect.

[0072] However, the comparative examples are obviously inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the ratio of the surfactant is changed, and in comparative example 2, the type of the surfactant is changed. It can be seen that the adsorption capacity of neon gas at low pressure (100Pa) decreases. In comparative example 3, the types of mixed microorganisms are different. In comparative example 6, no fermentation treatment is performed, and the neon gas adsorption amount of the porous adsorption material under 10000Pa conditions decreases; in comparative example 4, the stirring and impregnation conditions are different, and the adsorption amount under different pressures decreases, indicating that the stirring and impregnation conditions will affect the pore-forming effect of the in-situ directional activation of metal ions. In comparative example 5, the high-temperature activation conditions are different, and the adsorption amount under different pressures decreases, indicating that the high-temperature activation conditions will affect the structure of the porous adsorption material, thereby affecting the adsorption effect. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0073] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a porous adsorption material for removing neon from helium, characterized in that: The following steps are involved: (1) crushing the lignin raw material to obtain a powder; mixing 20-30 parts of the powder with 40-50 parts of deionized water by weight to obtain a fermentation material, inoculating the fermentation material with mixed microorganisms for aerobic fermentation, filtering, drying, crushing, screening, and obtaining a fermented lignin raw material; the mixed microorganisms include Bacillus licheniformis, Bacillus subtilis, and Rhizopus oryzae; (2) Mixing 1 part by weight of the fermented lignin raw material and 10-12 parts by weight of hydrochloric acid, ultrasonically dispersing for 40-50 minutes, stirring at 80-85° C. for 25-30 hours, washing with deionized water until neutral, and vacuum drying to obtain a carbon precursor; (3) placing the carbon precursor in a mixed solution containing a metal salt and a surfactant and stirring and impregnating the mixture to obtain a metal salt-impregnated carbon precursor; (4) washing the carbon precursor impregnated with the metal salt to remove the excess deposited metal salt, and drying to obtain a cleaned carbon precursor; (5) The cleaned carbon precursor is activated with carbon dioxide to form pores, thereby obtaining a porous adsorption material for removing neon from helium.

2. The method for preparing a porous adsorbent material for removing neon from helium according to claim 1, characterized in that: The lignin raw material in step (1) comprises coconut shell, olive shell and bamboo in a weight ratio of 1: (1.3-1.5): (0.5-0.7).

3. The method for preparing a porous adsorbent material for removing neon from helium according to claim 1, characterized in that: The amount of Bacillus licheniformis used in step (1) is 10 8 -10 9 CFU / mL fermentation feed; the dosage of Bacillus subtilis is 10 6 -10 7 CFU / mL fermentation feed; the dosage of Rhizopus oryzae is 10 6 -10 7 CFU / mL fermentation feed.

4. The method for preparing a porous adsorbent material for removing neon from helium according to claim 1, characterized in that: The fermentation conditions in step (1) are: fermentation at 32-35° C. for 5-8 hours.

5. The method for preparing a porous adsorbent material for removing neon from helium according to claim 1, characterized in that: The surfactant in step (3) comprises sodium dodecylbenzene sulfonate, octadecyl dimethyl betaine and a zwitterionic surfactant in a weight ratio of 1: (1.2-1.4): (0.3-0.5).

6. The method for preparing a porous adsorbent material for removing neon from helium according to claim 5, characterized in that: The preparation method of the zwitterionic surfactant comprises the following steps: Step 1: Heat the HCl aqueous solution to 40-45°C, add N,N-dimethylhexadecylamine dropwise, keep warm for 1-1.5h, then add ethanol solution of epoxidized soybean oil dropwise, control the temperature at 50-55°C, react for 6-8h, remove ethanol and water by vacuum distillation, and obtain soybean oil-based butylamine salt; in terms of molar ratio, N,N-dimethylhexadecylamine: HCl: epoxidized soybean oil = 3:3: (0.8-1); Step 2: Dissolve 10 parts by weight of soybean oil octylamine salt in ethanol aqueous solution, add 0.5-0.7 parts by weight of NaOH, reflux and stir for 4-6 hours, stop the reaction, filter, wash the filter residue with anhydrous ethanol, and vacuum dry to obtain a zwitterionic surfactant.

7. The method for preparing a porous adsorbent material for removing neon from helium according to claim 1, characterized in that: The metal salt in step (3) is selected from one or more of sodium salt, potassium salt, magnesium salt and zinc salt; the concentration of the metal salt in the mixed solution is 1-5 mol / L.

8. The method for preparing a porous adsorbent material for removing neon from helium according to claim 1, characterized in that: The stirring and impregnation conditions described in step (3) are: impregnation time is 20-24h, temperature is 60-80°C, stirring speed is 200-300rpm; the impregnation solid-liquid ratio of the carbon precursor and the mixed solution is 1:15-1:20g / mL.

9. The method for preparing a porous adsorbent material for removing neon from helium according to claim 1, characterized in that: In the step (5), the activation pore-forming process is to heat the cleaned carbon precursor and use carbon dioxide to activate the pore-forming process, the heating rate is 5-10°C / min, the activation temperature is 800-1000°C, the activation time is 80-100min, and the carbon dioxide concentration is 80-100%.

10. A porous adsorption material for removing neon from helium obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Porous activated carbon material as well as preparation method and application thereof

    CN114572980A

  • Low-temperature pressure swing adsorption method for efficiently removing neon and hydrogen from helium

    CN117753170A

  • Porous adsorption material for removing trace propane in monofluoromethane as well as preparation method and application of porous adsorption material

    CN118698500A

  • Biofuel production using biofilm in fermentation

    WO2012083244A2